Analysis of Economic Growth Determination and Invesment Needs in North Lombok - Sucipto, Bambang; Hailuddin, Hailuddin; Harsono, Iwan (Universitas Negeri Malang, 2018)
The purpose of this research aiming at (1) analyzing how big influence of labor, private investment and government expenditure (capital expenditure) to the economic growth of North Lombok Regency, and (2) understanding the amount of Investment need to achieve economic growth in North Lombok Regency. This research undergo a quantitative approach by using time series data source during 2009-2016 from Bureau Central of Statistics (BPS) and documents sourced from both the local government of North Lombok Regency and various publication papers. The analysis technique used in this research is Multiple Linear Regression and Incremental Capital Output Ratio (ICOR) Analysis. The findings indicate that, partially, variable of investment and government expenditure did not significantly affect to the economic growth. While labor have a positive relationship and significantly to the economic growth of North Lombok Regency. Simultaneously, Investment, capital expenditure and workforce amount have a significant effect to GDP growth.Keywords: Economic growth; investment; GDPJEL Codes: R11, R53